The effect of prolonged use of face mask on the changes in Tear-Film Status and Ocular Surface Disease Index Score - خضور, محمد; يوسف, حبيب; درويش, تيم (Latakia University Journal -Medical Sciences Series, 2023)
Purpose: To evaluate tear film stability, tear secretion volume, and dry eye symptoms according to the daily duration of wearing a face mask. Methods: In this cross-sectional comparative study, dry eye measurements were taken for 122 patients who wore medical face masks attending the ophthalmology clinic at Tishreen University Hospital in Lattakia during the time period 2022-2023.The research sample was divided into five groups according to the duration of wearing the surgical face mask (< 2 hours, 2-4 hours, 4-6 hours, 6-8 hours, > 8 hours). Tear film breakup time using slit lamp, Schirmer 1 test and Ocular Surface Disease Index. )OSDI.( Results: We noticed an increase in the severity of dry eye with increasing the duration of wearing, with statistically significant differences regarding the mean values of the Schirmer1 test, as it decreased with the increase in the duration of using a surgical face mask (p = 0.0001).The intensity of dry eye also increased with the increase in the wearing period, with statistically significant differences with respect to the mean values of the BUT tear film breakage time test, as it decreased with the increase in the duration of using the surgical face mask (p = 0.0001).The Ocular Surface Disease Index (OSDI) also showed an increase in the severity of dry eye as the wearing period increased, with statistically significant differences (p = 0.0001). Conclusion:The severity of dry eye increased with the increase in the duration of using the face mask in a statistically significant way. Key words: face mask, dry eye